PSYCHOEDUCATION THERAPY REDUCES FAMILY ANXIETY IN TREATING FAMILY MEMBER WHO SUFFERS FROM CATARACT - Siswoyo Siswoyo; Baskoro Setioputro; Cholil Albarizi (NurseLine Journal, 2016)
Anxiety will appear on the family in caring family member who suffers from cataract. Family psychoeducation therapy can help reduce anxiety, so that families can find a solution for family members who suffer from cataracts appropriately. The purpose of this study was to examine the effect of family psychoeducation therapy (FPE) on the anxiety level of family whose member suffers from cataract. This study was pre-experimental research with pretest-posttest design. The sampling technique was total sampling. There were 16 families of cataract patients living in the area of public health center of Jelbuk Jember participated in this research. Data collection was conducted in March 2016. FPE was given four times a week with a total of 12 times in 3 weeks and the duration was 60 minutes for each session. Zung Self-Rating Anxiety Scale (ZSAS) was applied to measure anxiety level. The result of data analysis using Kruskal Wallis test showed p value of 0.001 (α=0.05). There was a significant influence of family psychoeducation (FPE) therapy on the anxiety level of family whose member suffers from cataract. Psychoeducation therapy can increase knowledge and empowerment of families in caring for family members who suffer from cataracts. FPE consists of activities that can improve family adaptive functioning and skills of positive coping mechanisms. Psychoeducation therapy can be applied to families to lower the anxiety level from burden experienced in caring family members who suffer from cataracts.